Optically reversible electrical soft-breakdown in wide-bandgap oxides — a factorial study - Zhou, Yu (2019)
In an earlier work, we found that an electrical soft-breakdown region in wide-bandgap oxides, such as hafnium dioxide, silicon dioxide, etc., could be reversed when illuminated by white light. The effect is evidenced by a decrease in the breakdown leakage current, termed as a negative photoconductivity response. This finding raises the prospect for optical sensing applications based on these traditionally non-photo-responsive but ubiquitous oxide materials. In this study, we examine the statistical distribution for the rate of breakdown reversal as well as the influence of factors such as wavelength, light intensity, oxide stoichiometry (or oxygen content) and temperature on the reversal rate. The rate of breakdown reversal is shown to be best described by the lognormal distribution. Light in the range of ∼400–700 nm is found to have relatively little influence on the reversal rate. On the other hand, light intensity, oxygen content and temperature, each of them has a clear impact; a stronger light intensity, an oxide that is richer in oxygen content and a reduced temperature all speed up the reversal process substantially. These experimental results are consistent with the proposed phenomenological redox model involving photo-assisted recombination of the surrounding oxygen interstitials with vacancy defects in the breakdown path.